Frequency and Outcome of Metaplasia in Needle Biopsies of Prostate and Its Relation With Clinical Findings - Abdollahi, Alireza; Ayati, Mohsen (Urology Journal, 2009)
Introduction: Metaplasia is a reversible change in which one adult cell type is replaced by another adult cell type. Our aim was to determine the frequency and outcome of metaplasia in specimens from needle biopsies of the prostate and its relation with clinical findings. Materials and Methods: Among 1566 prostate specimens referred to 2 pathology centers of Tehran, we studied on cases with a diagnosis of metaplasia, during a 2-year period. The clinical and laboratory data of the patients with metaplasia were collected, and they were followed-up for 2 years. Age, serum total and free prostate-specific antigen levels, ultrasonography findings, and results of digital rectal examination were recorded at baseline and the follow-up period. Results: Ten prostate specimens (0.6%) had metaplasia, of which 6 were transitional and 4 were squamous metaplasia. Serum total PSA levels ranged from 0.7 ng/mL to 14.5 ng/mL, and free PSA levels ranged from 0.1 ng/mL to 1.3 ng/mL in the patients with metaplasia. None of the patients developed carcinoma of the prostate during the 2-year follow-up, and no significant changes were seen in the follow-up studies. Conclusion: Metaplasia of the prostate are often associated with BPH. Clinical findings on DRE and TRUS resemble those found in benign lesions of the prostate, such as BPH. We found no sign of developing malignancy in our 2-year follow-up. However, in the differential diagnosis of this benign lesion, malignant lesions, such as squamous cell carcinoma or urothelial transitional cell carcinoma, should also be taken into consideration.